Analysis of 10 Pediatric Nephrotic Syndrome Cases With Complications of Cerebral Sinovenous Thrombosis - Rong, Liping; Chen, Lizhi; Dong, Zhi; Zhuang, Hongjie; Lin, Zhilang; Mo, Ying; Jiang, Xiaoyun (Frontiers in Pediatrics, 2020)
Background: To analyze the clinical characteristics of nephrotic syndrome (NS) with complications of cerebral sinovenous thrombosis (CSVT) in children. Method: Clinical and radiographic, laboratory and treatment data obtained from 10 confirmed cases of NS with complications of CSVT were analyzed. All patients were followed up for at least 18 months. CSVT was diagnosed by cerebral computed tomography (CT) and/or magnetic resonance imaging (MRI) with or without magnetic resonance venography (MRV) of the cerebral vessels. Results: Among 10 cases reported, 4 were steroid-sensitive NS with frequent relapse, 5 were steroid-resistant (3 of them had renal biopsies showing 2 minimal change disease and one IgA nephropathy) and the other one was steroid-sensitive with one relapse. Common clinical manifestations were headache or ophthalmodynia complicated by vomiting, dizziness, convulsion and coma. Neuropathologic signs were positive in some cases. Papilledema appeared in only one case with winding of vein. Cerebrospinal fluid was examined in 3 cases with elevated pressure but normal cytological and biochemical results. D-dimer and fibrinogen levels were elevated while prothrombin time and activated partial thromboplastin time were shortened. 5 out of 7 cases who had performed cranial CT were suspicious for cerebral thrombosis. 9 cases had cranial MRI with abnormal signs in 7 cases. All of the cases received MRV confirming the diagnosis of CVST. Conclusion: Clinical manifestations of NS with CSVT are not specific but varied. Therefore CSVT should be considered once nervous manifestations present. MRV is a better method in diagnosis of CSVT.